2008
DOI: 10.1016/j.clay.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis and characterization of dioctahedral smectites: A montmorillonites series

Abstract: International audienceThe aim of this study is to synthesize and finely characterize montmorillonite samples, dioctahedral smectites without tetrahedral charges (structural formulae Nax(Al(2 − x)Mgx)Si4O10(OH)2), to allow their use as reference samples in clay science. The montmorillonites synthesis under hydrothermal conditions at different pressures and with various layer charge deficit has been attempted. The temperature was fixed at 320 °C, the pressure parameter values were 20 MPa, 80 MPa, 120 MPa and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 41 publications
3
26
0
2
Order By: Relevance
“…The most-studied natural montmorillonite is SWy-2 (Lantenois et al, 2008), and so research regarding nanocomposite preparation and characterization using this Wyoming montmorillonite is extensive, to say the least (for example, Kong and Park, 2003;Mansa and Detellier, 2013;Praus et al, 2013;Valandro et al, 2013). In this study, however, a cost-centric approach is employed to the preparation of polylactide nanocomposites by the characterization and use of the clay fraction of the Bragança formation, which is located in the north-eastern part of Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…The most-studied natural montmorillonite is SWy-2 (Lantenois et al, 2008), and so research regarding nanocomposite preparation and characterization using this Wyoming montmorillonite is extensive, to say the least (for example, Kong and Park, 2003;Mansa and Detellier, 2013;Praus et al, 2013;Valandro et al, 2013). In this study, however, a cost-centric approach is employed to the preparation of polylactide nanocomposites by the characterization and use of the clay fraction of the Bragança formation, which is located in the north-eastern part of Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies were summarized in a critical review by Kloprogge et al (1999). Using these stability fields as guidelines, it is possible to synthesize beidellites (Kloprogge et al, 1990(Kloprogge et al, , 1993Grauby et al, 1993), saponites (Suquet et al, 1977(Suquet et al, , 1982Grauby et al, 1993), hectorites (Torii et al, 1983;Torii, 1985;Torii andIwasaki, 1986, 1987), nontronites (Decarreau et al, 1987), and montmorillonites Yamada et al, 1991Yamada et al, , 1994Lantenois et al, 2007a). These last studies highlighted the difficulties involved in the synthesis of high-purity smectite with the desired chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Saponites with various layercharge deficits were synthesized and characterized by Suquet et al (1977). However, synthesis of montmorillonites with variable layer-charge deficits is difficult (Lantenois et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…The random assignment of substitutions and the first constraint that prohibits the presence of Mg-(OH) 2 -Mg pairs in the octahedral sheet are based on 1 H magic angle spinning nuclear magnetic resonance (MAS NMR) and FT-IR spectra from MMTs that show no contributions from Mg-(OH) 2 -Mg moieties and QM simulations that demonstrated that Mg 2+ substitutions are randomly distributed within the octahedral layer [35][36][37]. The second constraint, informed by the properties of synthetic MMTs [38][39][40][41], limits the substitution ratio of the edge PBC (i.e., Mg edge substitutions: total number of octahedral edge sites in the PBC) to less than 0.20, which is the maximum substitution ratio for a synthetic MMT with only octahedral substitutions. The structural characterization of synthetic MMTs with divalent cation substitution ratios greater than 0.20 revealed octahedral sheet occupancies greater than 2.00, which is indicative of an MMT structure with some trioctahedral character, and isomorphic substitutions in the tetrahedral sheet.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%